Preparation method of hybrid integrated circuit substrate bonding pad

By adopting two printing processes and high-temperature sintering technology in the preparation process of hybrid integrated circuit substrate pads, the problem of cracking of the pads in harsh environments is solved, and the stress resistance and service life of the pads are significantly improved.

CN119730040APending Publication Date: 2025-03-28JINZHOU 777 MICROELECTRONICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411925362.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The pads of hybrid integrated circuit substrates are prone to cracking in harsh environments, affecting the firmness and service life of the circuit.

Method used

Using two printing processes, the conductor slurry was leak-printed on the ceramic substrate through a 35μm film mesh plate and sintered at 850°C for 10 minutes to form a pad film layer with increased thickness, improving the stress resistance of the pad.

Benefits of technology

It significantly improves the physical strength and durability of the pad, enhances its resistance to stress shock, reduces the risk of pad cracking, and extends the service life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730040A_ABST
    Figure CN119730040A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a hybrid integrated circuit substrate bonding pad, which comprises the following steps of: aligning a pattern on a film screen with the thickness of 35 microns with a pattern on a ceramic substrate, printing conductor paste on the ceramic substrate through the film screen by using a scraper, then drying and sintering to form a first bonding pad film layer, and unloading the film screen after the printing is completed; and aligning the pattern on the film screen plate with the thickness of 35 microns with the ceramic substrate printed with the first bonding pad film layer again, performing skip printing on the conductor paste on the ceramic substrate again through the film screen plate by using the scraper, drying the secondarily printed film layer, and sintering at 850 DEG C for 10 minutes to obtain the hybrid integrated circuit substrate bonding pad. The method has the advantages that the process is simple, the operation is easy, the stress resistance of the bonding pad can be improved, the cracking risk of the bonding pad is reduced, and the practical application requirement is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a hybrid integrated circuit substrate pad. Background Art

[0002] In the assembly process of hybrid integrated circuits, key components such as resistors and capacitors are usually accurately and firmly soldered to thick film substrates using a reflow process. As a bridge between components and substrates, the pad functions as the foundation of a building, playing a vital role in supporting the entire circuit board and fixing components. Therefore, the quality of the pad directly determines the service life and performance of hybrid integrated circuit products.

[0003] In practical applications, hybrid integrated circuits often need to work in various harsh environments, such as continuous high-temperature and low-temperature cycle environments. Under such conditions, the pads will be affected by thermal expansion and contraction, and experience repeated tension. This long-term stress can easily cause the pads to crack, which in turn affects the firmness of the welding and the conductivity of the circuit. Pad cracking will not only reduce the performance of the product, but may also cause circuit failure, seriously shortening the service life of the product.

[0004] Generally speaking, hybrid integrated circuit substrate pads are generally screen printed. A scraper is used to pass the conductor paste through the film stencil on which the pad pattern has been made, so that it is evenly screen printed on the ceramic substrate, and then dried and sintered. After all the film layers of the substrate are completed, they are assembled. Reflow soldering process is usually used to solder components such as resistors and capacitors to the pads. In the subsequent use process, it is found that the pads have cracking problems. In order to eliminate this failure mode, the pad thickness is increased by increasing the thickness of the film stencil. Although the stress resistance performance is improved, the effect is not ideal. There are still problems of wrinkling and even cracking of the pads, which cannot meet the actual application requirements. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a hybrid integrated circuit substrate pad, which has a simple process and is easy to operate, can improve the stress resistance of the pad, reduce the risk of pad cracking, and meet practical application requirements.

[0006] The technical solution of the present invention is: A method for preparing a hybrid integrated circuit substrate pad, the specific steps of which are as follows: (1) Align the pattern on the 35 μm thick film stencil with the pattern on the ceramic substrate, use a scraper to print the conductive paste on the ceramic substrate through the film stencil, and then dry and sinter to form the first layer of the pad film layer. After printing, remove the film stencil; (2) The pattern on the 35 μm thick film stencil is aligned again with the ceramic substrate on which the first pad film layer has been printed, and the conductive paste is again printed on the ceramic substrate through the film stencil using a scraper. The second printed film layer is dried and sintered at 850° C. for 10 min to obtain the hybrid integrated circuit substrate pad.

[0007] Furthermore, in step (1) and step (2), the conductor paste is silver-palladium conductor paste.

[0008] Further preferably, the mass ratio of metallic silver to palladium in the conductive paste is 95:5.

[0009] Furthermore, in step (1) and step (2), the drying temperature is 150° C. and the drying time is 15 min.

[0010] Furthermore, in step (1), sintering is performed after drying to reduce defects and non-performing rates in the pad manufacturing process, thereby improving the overall yield rate.

[0011] More preferably, the sintering is carried out at 850° C. for 10 minutes.

[0012] The beneficial effects of the present invention are: (1) Compared with the traditional process of one printing and one firing, the film thickness of the pad is effectively increased by printing twice, which not only improves the physical strength and durability of the pad, but also significantly enhances its ability to resist stress impact, making the pad less likely to deform or crack when subjected to external pressure or impact.

[0013] (2) Using silver-palladium conductor paste with a mass ratio of metallic silver to palladium of 95:5 further reduces the risk of cracking of the pad, thereby improving the reliability and service life of the pad.

[0014] (3) Due to the improvement of pad performance, the failure rate of the product is reduced, thereby reducing maintenance costs and downtime; it has high promotion value in practical applications and can be widely used in various fields that require high-reliability pads, such as automotive electronics, aerospace, communication equipment, etc.

[0015] In summary, increasing the pad thickness combined with processing technology and conductor paste makes the pad show significant advantages in film thickness, stress impact resistance, welding performance, corrosion resistance, etc., reducing the risk of pad cracking and making the product more stable and reliable during long-term use. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a microscope photograph of the polished surface of the present invention (corresponding to Example 2); Figure 2 This is a microscopic photograph of the polished surface of the conductive paste A of the present invention (corresponding to Example 4). DETAILED DESCRIPTION

[0017] The embodiments and comparative examples of the present invention involve two film screens of different thicknesses, a 35 μm film screen and a 70 μm film screen. The 35 μm film screen is commercially available, and the 70 μm film screen is formed by laminating two 35 μm film screens.

[0018] Example 1 (1) This embodiment uses silver-palladium conductor paste, and the mass ratio of metal silver to palladium in the conductor paste is 95:5; (2) Align the pattern on the 35 μm thick film stencil with the pattern on the ceramic substrate. In this embodiment, 10 pad samples are prepared on the ceramic substrate, with 3 components soldered on each pad as an example. A scraper is used to print the conductive paste on the ceramic substrate through the film stencil, and then the film is dried at 150°C for 15 minutes to form the first pad film layer. After printing, the film stencil is removed; (3) The pattern on the 35 μm thick film stencil is aligned again with the ceramic substrate on which the first pad film layer has been printed. A scraper is used to print the conductive paste on the ceramic substrate through the film stencil again. The second printed film layer is dried at 150°C for 15 minutes and sintered at 850°C for 10 minutes (to form a pad metal film layer). A hybrid integrated circuit substrate pad is obtained, which is recorded as 35-D-2-1. The first-time qualified rate of the product is 80%.

[0019] Example 2 (1) The conductor paste of this embodiment is the same as that of Embodiment 1 (silver-palladium conductor paste is used, and the mass ratio of metal silver to palladium in the conductor paste is 95:5); (2) Align the pattern on the 35 μm thick film stencil with the pattern on the ceramic substrate. In this embodiment, 10 pad samples are prepared on the ceramic substrate, each with 3 components. A scraper is used to print the conductive paste on the ceramic substrate through the film stencil, and then dried at 150° C. for 15 minutes and sintered at 850° C. for 10 minutes to form the first pad metal film layer. After printing, the film stencil is removed; (3) The pattern on the 35 μm thick film stencil is aligned again with the ceramic substrate on which the first layer of the pad metal film layer has been printed, and the conductive paste is again printed on the ceramic substrate through the film stencil using a scraper. The second printed film layer is dried at 150° C. for 15 min and sintered at 850° C. for 10 min (to form the second layer of the pad metal film layer), thereby obtaining the hybrid integrated circuit substrate pad, which is recorded as 35-D-2-2. The first-time qualified rate of the product is 100%.

[0020] In order to compare the use of different conductive pastes to make pads in the present invention, Comparative Examples 1 to 4 use different conductive pastes to conduct parallel tests, where: (1) Conductor paste A: silver-palladium conductor paste, the mass ratio of metal silver to palladium in the conductor paste is 85:15, and the rest is the same as in Example 1; (2) Conductive paste B: silver-palladium conductive paste, the mass ratio of metal silver, palladium and platinum in the conductive paste is 66.7:27:6.3, and the rest is the same as in Example 1; (3) Conductor paste C: silver-platinum conductor paste, the mass ratio of metal silver to platinum in the conductor paste is 99.5:0.5, and the rest is the same as in Example 1; (4) Conductive paste D: the conductive paste of Example 1.

[0021] Comparative Example 1: One Printing and One Burning Process The pattern on the 35 μm thick film stencil is aligned with the pattern on the ceramic substrate. In this embodiment, 10 pad samples are prepared on the ceramic substrate, and 3 components are soldered on each pad. The conductor paste is printed on the ceramic substrate through the 35 μm thick film stencil with a scraper. After printing once, it is dried at 150° C. for 15 minutes, and then sintered at 850° C. for 10 minutes to obtain the hybrid integrated circuit substrate pad; Selection of conductor pastes in this comparative example: (1) conductor paste A, denoted as 35-A-1; (2) conductor paste B, denoted as 35-B-1; (3) conductor paste C, denoted as 35-C-1; (4) conductor paste D, denoted as 35-D-1; 10 pad samples were prepared with each conductor paste according to the above method, and the metal film thickness data of each 35μm thick film stencil one print one burn pad are as follows (measured by X-RAY method): Table 1 Thickness data of metal film layer of 35μm film stencil one print one burn pad Conductive paste 1 2 3 4 5 6 7 8 9 10 A 9.93μm 10.1μm 9.86μm 10.1μm 10.0μm 9.48μm 10.1μm 9.80μm 9.75μm 9.87μm B 9.47μm 10.2μm 10.4μm 10.0μm 9.67μm 10.1μm 10.7μm 10.2μm 10.5μm 10.4μm C 10.3μm 9.62μm 9.45μm 9.89μm 10.05μm 9.71μm 9.93μm 10.54μm 10.01μm 10.36μm D 10.5μm 9.90μm 10.22μm 9.62μm 9.90μm 9.87μm 9.88μm 10.17μm 9.97μm 10.44μm Random inspection: 3 reflow soldered capacitor components were randomly selected from 10 samples of hybrid integrated circuit substrate pads in Comparative Example 1, and then subjected to temperature cycle test at -65℃~150℃, 100 times, and the state of the pads was observed under a 30x microscope: (1) Sample 35-A-1, the pad has wrinkles and a tendency to break, and the test will continue after increasing the thickness; (2) Sample 35-B-1, the pad edge is lifted and separated from the bottom ceramic substrate. Analysis shows that the material has insufficient adhesion and needs to be verified by increasing the thickness; (3) Sample 35-C-1, no obvious change in the pad; (4) Sample 35-D-1, no obvious change in the pad.

[0022] Comparative Example 2: One Printing and One Burning Process The pattern on the 70 μm thick film stencil is aligned with the pattern on the ceramic substrate. In this embodiment, 10 pad samples are prepared on the ceramic substrate, and 3 components are soldered on each pad. The conductive paste is printed on the ceramic substrate through the 70 μm thick film stencil with a scraper. After printing once, it is dried at 150° C. for 15 minutes, and then sintered at 850° C. for 10 minutes to obtain the hybrid integrated circuit substrate pad. Selection of conductor pastes in this comparative example: (1) conductor paste A, denoted as 70-A-1; (2) conductor paste B, denoted as 70-B-1; (3) conductor paste C, denoted as 70-C-1; (4) conductor paste D, denoted as 70-D-1; 10 pad samples were prepared using each conductor paste according to the above method, and the metal film thickness data of each pad prepared by printing and firing a 70 μm thick film stencil is as follows (measured by X-RAY method): Table 2 Thickness data of metal film layer of 70μm film stencil one print one burn pad Conductive paste 1 2 3 4 5 6 7 8 9 10 A 15.4μm 16.2μm 17.2μm 17.1μm 18.4μm 15.2μm 15.5μm 17.7μm 17.2μm 18.4μm B 15.3μm 15.1μm 17.6μm 17.3μm 18.9μm 16.0μm 15.6μm 16.7μm 17.0μm 18.4μm C 16.2μm 15.2μm 16.8μm 17.4μm 17.4μm 16.5μm 16.9μm 16.7μm 17.0μm 18.5μm D 16.1μm 16.3μm 17.5μm 17.3μm 18.4μm 15.2μm 17.7μm 17.7μm 18.3μm 17.7μm Random inspection: 3 reflow soldering capacitor components were randomly selected from 10 hybrid integrated circuit substrate pad samples in Comparative Example 2 and subjected to temperature cycle test. The test temperature was -65℃~150℃, and the number of times was 100. The state of the pad was observed under a 30x microscope: (1) Sample 70-A-1, the pad condition is significantly stronger than that of sample 35-A-1, the thickening is effective, and there are slight wrinkles at the pad; (2) Sample 70-B-1: The phenomenon is the same as sample 35-B-1. The edge of the pad is lifted and separated from the bottom ceramic substrate. (3) Sample 70-C-1, no obvious change in the pad; (4) Sample 70-D-1, no obvious change in the pad.

[0023] Comparative Example 3: Two Prints and One Burn (1) Align the pattern on the 35 μm thick film stencil with the pattern on the ceramic substrate. In this embodiment, 10 pad samples are prepared on the ceramic substrate, each with 3 components. A scraper is used to print the conductive paste on the ceramic substrate through the film stencil, and then the film is dried at 150° C. for 15 minutes to form the first pad film layer. After the printing is completed, the film stencil is removed; (2) Align the pattern on the 35 μm thick film stencil with the ceramic substrate on which the first pad film layer has been printed again, and a scraper is used to print the conductive paste on the ceramic substrate through the film stencil again. The second printed film layer is dried at 150° C. for 15 minutes and sintered at 850° C. for 10 minutes to obtain a hybrid integrated circuit substrate pad; Selection of conductor paste in this comparative example: Among them, conductor paste A is recorded as 35-A-2-1; conductor paste B is recorded as 35-B-2-1; conductor paste C is recorded as 35-C-2-1; each conductor paste is used to make 10 pads according to the above method, and the metal film layer thickness data of each pad made by two printings and one firing of a 35μm thick film stencil is as follows (measured by X-RAY method): Table 3 Thickness data of metal film layer of 35μm thick film stencil double print and one burn pad Conductive paste 1 2 3 4 5 6 7 8 9 10 A 16.6μm 16.1μm 18.0μm 18.8μm 17.4μm 16.1μm 15.3μm 17.3μm 16.6μm 17.9μm B 15.8μm 16.1μm 16.8μm 17.2μm 18.9μm 15.8μm 15.6μm 17.2μm 18.0μm 18.2μm C 15.7μm 16.7μm 17.8μm 18.3μm 17.6μm 16.0μm 15.7μm 17.0μm 16.9μm 18.3μm Example 1 16.1μm 16.0μm 16.7μm 16.9μm 18.6μm 16.0μm 16.7μm 17.8μm 17.8μm 18.0μm Random inspection: 3 reflow soldering capacitor components were randomly selected from 10 samples of hybrid integrated circuit substrate pads in Comparative Example 3 and Example 1, and then subjected to temperature cycle test. The test temperature was -65°C to 150°C, and the number of times was 100. The state of the pads was observed under a 30x microscope: (1) Sample 35-A-2-1, slight wrinkles on the pad; (2) Sample 35-B-2-1: Similarly, the pad edge is lifted and separated from the bottom ceramic substrate; (3) Sample 35-C-2-1, no obvious change in the pad; (4) Sample 35-D-2-1, no obvious change in the pad.

[0024] Comparative Example 4: Two Prints and Two Fires: (1) Align the pattern on the film stencil with a thickness of 35 μm with the pattern on the ceramic substrate. In this embodiment, 10 pad samples are prepared on the ceramic substrate, and 3 components are soldered on each pad. The conductive paste is printed on the ceramic substrate through the film stencil with a scraper, and then dried at 150° C. for 15 minutes and sintered at 850° C. for 10 minutes to form the first pad metal film layer. After printing, the film stencil is removed; (2) aligning the pattern on the 35 μm thick film stencil with the ceramic substrate on which the first pad metal film layer has been printed again, and using a scraper to print the conductive paste on the ceramic substrate again through the film stencil, drying the second printed film layer at 150° C. for 15 min, and sintering at 850° C. for 10 min, to obtain a hybrid integrated circuit substrate pad; Selection of conductor paste in this comparative example: Among them, conductor paste A is recorded as 35-A-2-2; conductor paste B is recorded as 35-B-2-2; conductor paste C is recorded as 35-C-2-2; each conductor paste is used to make 10 pad samples according to the above method, and the total thickness data of the metal film layer of each pad made by two printings and two firings of a 35μm thick film screen is as follows (measured by X-RAY method): Table 4 Total thickness data of metal film layer of 35μm film stencil double printing and double firing pad Conductive paste 1 2 3 4 5 6 7 8 9 10 A 15.5μm 16.5μm 17.4μm 17.6μm 18.4μm 17.0μm 17.3μm 18.3μm 17.9μm 18.7μm B 15.8μm 16.0μm 17.3μm 18.7μm 17.2μm 16.8μm 16.3μm 18.1μm 18.0μm 17.6μm C 15.6μm 16.7μm 17.4μm 18.3μm 18.7μm 17.8μm 16.3μm 17.9μm 18.2μm 17.8μm Example 2 15.3μm 16.8μm 18.2μm 17.3μm 18.9μm 17.3μm 16.6μm 17.7μm 18.0μm 18.6μm Random inspection: 3 reflow soldered capacitor components were randomly selected from 10 samples of hybrid integrated circuit substrate pads in Comparative Example 4 and Example 2 and subjected to temperature cycle test at -65°C to 150°C for 100 times, and the state of the pads was observed under a 30x microscope.

[0025] (1) Sample 35-A-2-2, slight wrinkles on the pad; (2) Sample 35-B-2-2: Similarly, the pad edge is lifted and separated from the bottom ceramic substrate; (3) Sample 35-C-2-2, no obvious change in the pad; (4) Sample 35-D-2-2, no obvious change in the pad.

[0026] In summary, among the 16 samples in Example 1 and Example 2 of the present invention and Comparative Examples 1-4, under the test temperature of -65°C to 150°C and 100 temperature cycle tests, the edges of the pads of the B material samples all have different degrees of warping, and the B material is the worst; the 35-A-1 of the A material is not as good as the 70-A-1, 35-A-2-1 and 35-A-2-2 with thickened pads; the C material and the D material are both acceptable at present.

[0027] The three groups of samples 70-A-1, 35-A-2-1 and 35-A-2-2 with thickened pads of material A continued the temperature cycle test. All samples of materials C and D continued the temperature cycle test at the same time. The test temperature was -65℃~150℃, and the number of times was 100 times (that is, a total of 200 temperature cycles at this time). The state of the pads was observed under a 30x microscope: (1) Conductor paste A, there are tiny wrinkles at the pad; (2) Conductor paste C shows obvious signs of warping, and its development trend is the same as that of material B; (3) Conductive paste D, no obvious wrinkles at the pad.

[0028] It can be seen that as the temperature cycle test continues, conductor paste C approaches the development state of material B, and conductor paste C is worse. At this time, conductor paste A and conductor paste D are both better than conductor paste C, and conductor paste D has a better effect.

[0029] Three methods of increasing the film thickness, 70μm film stencil one print and one burn, 35μm film stencil two prints and one burn, 35μm film stencil two prints and two burns, all improve conductor paste A and conductor paste D, and conductor paste D is better.

[0030] 1. Strengthening test on hybrid integrated circuit substrate pads prepared with conductive paste A and conductive paste D (1) There are six groups of samples for the strengthening test of conductive paste A and conductive paste D, namely 70-A-1 sample, 70-D-1 sample, 35-A-2-1 sample, 35-D-2-1 sample, 35-A-2-2 sample, and 35-D-2-2 sample.

[0031] (2) In the above-mentioned embodiments 1-2 and comparative examples 2-4, 6 pad samples were randomly selected from the remaining 7 pad samples and then the capacitor components were reflowed normally for simulation screening, mechanical environment test and high temperature storage test. The samples for the mechanical environment test and high temperature storage test were all the samples after simulation screening. The specific experimental process is shown in Table 5: Table 5 Pad reinforcement test results (1) Simulation screening test There was no obvious difference in the samples after the simulated screening under a 30x microscope, so the subsequent tests were continued; After all the samples have undergone simulation screening, they are divided into two groups with 3 samples in each group for testing. One group undergoes mechanical environment testing, and the other group undergoes high-temperature storage testing. The tests are all based on the relevant requirements of GJB2438.

[0032] (2) Mechanical environmental test After the mechanical environmental test, the state of the sample pads was observed under a 30x microscope, and the difference was not obvious; 8 of the 9 components of the 3 pad samples were subjected to shear strength tests, and 1 component was subjected to grinding tests. The shear strength data after the mechanical environmental test are shown in Table 6: Table 6 Shear strength data of 8 components of 3 pad samples after mechanical environmental testing It can be seen from Table 6 that after the shear strength test, the conductor paste A is not as good as the conductor paste D. Under the same material, the 70μm film stencil one print and one burn is not as good as the 35μm film stencil two prints and one burn and the 35μm film stencil two prints and two burns.

[0033] The remaining component that was not subjected to the shear strength test was further subjected to a grinding test, and the polishing state of the pad after reflow was observed under a microscope. Figure 1 and Figure 2As shown. The edge of the pad of conductor paste A is fractured, while the pad of conductor paste D is intact, and the boundary between the pad and the solder is clearly visible. It can be seen that conductor paste A is not as good as conductor paste D in terms of its ability to resist mechanical environmental stress. Observing the polished surface with a microscope mainly focuses on the interface between the reflow solder paste and the pad, which can reflect the effect of the solder paste on the pad material. The interface of conductor paste D is clear, the solder paste penetrates less into the pad film layer, and the effect is relatively small, so the risk of pad cracking in the later stage is low; the interface of conductor paste A is unclear, and the solder paste almost completely penetrates into the pad film layer, so the effect is relatively large, and the pad has cracked under harsh mechanical environments.

[0034] (3) High temperature storage test After high temperature storage at 125℃ for 1000h, the state of the pad was observed under a 30x microscope and no abnormality was found. The shear strength test was carried out on 8 components of 3 pad samples. The shear strength data after high temperature storage at 125℃ for 1000h are shown in Table 7: Table 7 Shear strength data of 8 components of 3 pad samples after high temperature storage It can be seen from Table 7 that the three samples of conductor paste A are not as good as the state of conductor paste D, and the 70μm film stencil one print and one burn is not as good as the 35μm film stencil two prints and one burn and the 35μm film stencil two prints and two burns. At the same time, the effect of solder paste on the pad after high-temperature storage and reflow is also significantly different. For the pad made with conductor paste D, the solder paste does not act on the edge of the pad, and there is no wrinkle caused by stress interaction; for the pad made with conductor paste A, the solder paste can act on the edge of the pad, and after the stress interaction produces wrinkles, the pad will eventually crack over time.

[0035] In summary, it can be concluded from the mechanical environment test and high temperature storage test that the shear strength data can show that conductor paste D is better than conductor paste A.

[0036] The present invention increases the thickness of the film stencil and the number of printing passes, which can increase the thickness of the pad and improve the solder resistance. The method of increasing the thickness of the pad by printing twice is better than thickening the film stencil to thicken the pad once; printing twice can avoid the problem of insufficient density of the film layer caused by directly increasing the thickness of the 70μm film stencil; but since the second printing pattern is incompletely reworked during the two-printing and one-firing, the film layer printed in the first pass has not yet been sintered and formed, and rework at this time will damage the first film layer, which is not convenient for actual production and is not conducive to production, resulting in a reduction in the first-time qualified rate of the product; two-printing and two-firing can avoid the problem of difficulty in rework during two-printing and one-firing. And while two-printing and two-firing increases the thickness of the film layer, the actual operation is simple and feasible, which is conducive to production, and the two-printing and two-firing process method is the best. When using the reflow soldering process to solder resistors and capacitors, the conductor paste D is the best. When experiencing harsh mechanical environments and long-term high temperatures, on the basis of meeting the shear strength requirements, the reliability of the pad is improved, and problems such as cracking are solved from the source.

[0037] The above are only specific embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a hybrid integrated circuit substrate pad, characterized in that: The specific steps are as follows: (1) Align the pattern on the 35 μm thick film stencil with the pattern on the ceramic substrate, use a scraper to print the conductive paste on the ceramic substrate through the film stencil, and then dry it to form the first layer of pad film. After printing, remove the film stencil; (2) The pattern on the 35 μm thick film stencil is aligned again with the ceramic substrate on which the first pad film layer has been printed, and the conductive paste is again printed on the ceramic substrate through the film stencil using a scraper. The second printed film layer is dried and sintered at 850° C. for 10 min to obtain the hybrid integrated circuit substrate pad.

2. The method for preparing a hybrid integrated circuit substrate pad according to claim 1, wherein: In step (1) and step (2), the conductor paste is silver-palladium conductor paste.

3. The method for preparing a hybrid integrated circuit substrate pad according to claim 2, wherein: The mass ratio of metallic silver to palladium in the conductive paste is 95:

5.

4. The method for preparing a hybrid integrated circuit substrate pad according to claim 1, wherein: In step (1) and step (2), the drying temperature is 150° C. and the drying time is 15 min.

5. The method for preparing a hybrid integrated circuit substrate pad according to claim 1, wherein: In step (1), sintering is performed after drying.

6. The method for preparing a hybrid integrated circuit substrate pad according to claim 6, wherein: Sintered at 850°C for 10 min.